Manajemen Lembaga Dakwah FKUB dalam Mewujudkan Moderasi Beragama di Kota Medan - Arsyad, Agam; Hasibuan, Wildan Ansori; Primadani, Rizky (Khazanah : Journal of Islamic Studies, 2024)
This study examines the management strategies of the Forum Kerukunan Umat Beragama (FKUB) in promoting religious moderation in the multicultural society of Medan City. As a key institution fostering interfaith harmony, FKUB utilizes managerial functions—planning, organizing, implementing, and evaluating—to design and execute programs such as interfaith seminars, conflict mediation, and capacity building for religious leaders. Employing a qualitative descriptive approach, the research explores the challenges and impacts of these strategies through in-depth interviews, participatory observations, and document analysis. Results indicate that while FKUB's programs significantly enhance interfaith communication and reduce religious tensions, challenges such as societal resistance to moderation concepts, limited funding, and low community participation hinder broader implementation. This study underscores the importance of enhancing FKUB’s resource capacity and outreach strategies to strengthen social harmony. The findings provide practical recommendations for FKUB and similar institutions to effectively implement religious moderation programs within diverse communities.